A magnetic prepreg of a PCB board of a planar transformer and a preparation method thereof

By using magnetic semi-cured sheets on the PCB board of the planar transformer, the problem of low efficiency at high power density is solved, the combination of high voltage with high magnetic permeability is achieved, and the overall thermal conductivity and efficiency are improved.

CN115175446BActive Publication Date: 2025-04-22GUANGDONG PRECISION DRAGON ELECTRONIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211020366.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-24
Publication Date
2025-04-22
Estimated Expiration
2042-08-24

AI Technical Summary

Technical Problem

Existing planar transformers are difficult to meet the demand for efficiency under high power density, and due to the high copper wire loss, the resistance is higher and the efficiency is affected.

Method used

By filling a magnetic material and covering a silicon dioxide layer, optimizing the resin composition, a magnetic semi-cured sheet with high pressure and magnetic permeability is prepared for a PCB board for a planar transformer.

Benefits of technology

It realizes maintaining a certain magnetic permeability at high voltage level, meeting the high efficiency needs under high power density, and at the same time improves thermal conductivity and reduces the heat dissipation obstacles of copper lines.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a magnetic semi-cured sheet of a PCB board of a planar transformer and a preparation method thereof, the method comprising the following steps: S1: coating a layer of silicon dioxide layer on a magnetic material with a particle size less than 20 μm to form a coated powder; S2: mixing the coated powder with an oxide, epoxy resin, polyester resin, anhydride catalyst, and paraffin with a particle size less than 5 μm; obtaining a mixed powder; S3: heating and stirring the mixed powder evenly under an inert gas atmosphere, and after cooling, crushing it into powder to obtain a granulated powder; the heating temperature is greater than the melting temperature of paraffin; S4: the granulated powder is pressed and formed under a pressure of 10-100 MPa to obtain a magnetic sheet embryo; S5: semi-curing the magnetic sheet embryo to form a magnetic semi-cured sheet. Since the magnetic semi-cured sheet contains magnetic material and the magnetic material is coated with silicon dioxide, it can have magnetism while satisfying insulation, so it can meet the current demand for high efficiency of switching power supplies at high power density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of planar transformers, and in particular to a magnetic prepreg of a PCB board of a planar transformer and a preparation method thereof. Background Art

[0002] In recent years, with the development of communications and consumer electronics, higher requirements have been put forward for the application of low-power power supplies, especially the requirements for high power density and high efficiency are getting higher and higher. Planar transformers have been widely used due to their small size, high utilization rate and good heat dissipation. As the applied current gradually increases, how to reduce copper wire loss has become one of the characteristics to be upgraded. The existing planar transformers are realized by assembling magnetic cores and PCB boards. The PCB board occupies a certain magnetic space, resulting in the need for more copper wires to meet the needs of the transformer, but this will cause the copper wire to have a higher resistance, and simply adding metal materials to the PCB will easily lead to insufficient voltage breakdown resistance of the PCB. Therefore, it is very necessary to develop new PCB board materials with magnetic properties for planar transformers.

[0003] Therefore, the prior art has defects and needs to be improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is: to provide a magnetic prepreg of a PCB board of a planar transformer and a preparation method thereof, by designing the filling magnetic material and grading the powder and optimizing the resin composition, the obtained magnetic prepreg maintains a certain magnetic permeability at a higher withstand voltage level, thereby meeting the current demand for high efficiency of switching power supplies at high power density.

[0005] The technical solution of the present invention is as follows: a method for preparing a magnetic prepreg of a PCB board of a planar transformer is provided, comprising the following steps.

[0006] S1: A layer of silicon dioxide is coated on a magnetic material with a particle size less than 20 μm to form a coated powder. The composition of the magnetic material is 79.6-86.85wt% Fe, 6.5-9.5wt% Si, 5.5-7.5wt% Cr, 1.0-3.0wt% B, 0.05-0.2wt% Al, 0.05-0.1wt% C, 0.05-0.1wt% Mn. The role of Al and Mn elements is to improve the insulation of the magnetic material powder, because in the process of preparing the magnetic material powder, Al and Mn elements are easy to precipitate on the surface of the magnetic material powder to form corresponding oxides, thereby improving the insulation of the magnetic material powder. The role of C element is: C element is used to protect the a-Fe crystal phase from being easily transformed and maintain the magnetism of the magnetic material. The preparation method of the coated powder is as follows: the magnetic material and the hydrolysis component are mixed to undergo a hydrolysis reaction at 35-75°C, and then dried to form the coated powder; wherein the hydrolysis component is tetraethyl orthosilicate, ammonia water, a surfactant, an alcohol solvent, an alkane solvent, and water; wherein the amount of tetraethyl orthosilicate added is 0.3wt% to 2.0wt% of the magnetic material, wherein the amount of ammonia water added is 0.05wt% to 0.1wt% of the magnetic material, wherein the amount of the surfactant added is 0.5wt% to 2.5wt% of the magnetic material, wherein the amount of the alcohol solvent added is 2wt% to 5wt% of the magnetic material, wherein the amount of the alkane solvent added is 10wt% to 20wt% of the magnetic material, wherein the amount of water added is 0.5wt% to 2.0wt% of the magnetic material. The specific steps of step S1 are: S11: mixing magnetic powder, surfactant, alcohol solvent, alkane solvent and water and stirring to prepare a microemulsion containing magnetic powder; S12: adding tetraethyl orthosilicate to the microemulsion containing magnetic powder and continuing to stir; S13: adding ammonia water to hydrolyze tetraethyl orthosilicate and coating a silicon dioxide layer on the surface of the magnetic material. The surfactant is phenyl-polyethylene glycol, the alcohol solvent is n-hexanol, and the alkane solvent is cyclohexane.

[0007] Coating a layer of silicon dioxide on the surface of the magnetic material can effectively improve the insulation performance between the magnetic material particles. After mixing and stirring the magnetic powder, surfactant, alcohol solvent, alkane solvent and water to make a microemulsion containing magnetic powder, and then adding tetraethyl orthosilicate and ammonia water for hydrolysis, the silicon dioxide layer coated on the surface of the magnetic material obtained after the hydrolysis of tetraethyl orthosilicate can be made more uniform, ensuring that the performance of the coated powder is basically consistent.

[0008] S2: Mix the coated powder with oxides with a particle size of less than 5 μm, epoxy resin, polyester resin, anhydride catalyst, and paraffin wax to obtain a mixed powder. The oxide is silicon oxide and / or aluminum oxide, and the amount of the oxide added is 10wt% to 20wt% of the coated powder, wherein the amount of epoxy resin added is 5wt% to 15wt% of the coated powder, wherein the amount of polyester resin added is 5wt% to 15wt% of the coated powder, wherein the amount of anhydride catalyst added is 0.01wt% to 0.1wt% of the coated powder, and wherein the amount of paraffin added is 0.5wt% to 2.0wt% of the coated powder. Epoxy resin, polyester resin, and anhydride catalyst are the raw materials of ordinary semi-cured sheets. By adding oxides, the insulation performance of the manufactured PCB can be further improved.

[0009] S3: Heat and stir the mixed powder in an inert gas atmosphere to make it uniform, and after cooling, crush it into powder to obtain granulated powder; the heating temperature is greater than the melting temperature of paraffin. The mixed powder is heated and stirred in an inert gas atmosphere for 1 to 5 hours, and the particle size of the granulated powder is 50um to 300um; the inert gas is nitrogen. The paraffin can improve the fluidity of epoxy resin, polyester resin, and acid anhydride catalyst under heating conditions, so that the components are mixed uniformly. The nitrogen is used to inhibit the curing of epoxy resin, polyester resin, and acid anhydride catalyst.

[0010] S4: The granulated powder is pressed into a shape at a pressure of 10-100 MPa to obtain a magnetic sheet embryo.

[0011] S5: semi-curing the magnetic sheet embryo under an inert gas atmosphere at 140-250° C. to form a magnetic semi-cured sheet. The inert gas is nitrogen. At a temperature of 140-250° C., the magnetic sheet embryo can be semi-cured in the inert gas to form a magnetic semi-cured sheet.

[0012] The present invention also provides a magnetic semi-cured sheet for a PCB board of a planar transformer, which is made by the aforementioned method for preparing a magnetic semi-cured sheet for a PCB board of a planar transformer. The magnetic semi-cured sheet can be used to make a PCB board of a planar transformer. Since the magnetic semi-cured sheet contains magnetic material, and the magnetic material is coated with silicon dioxide, it can have magnetism while satisfying insulation, so it can meet the current demand for high efficiency of switching power supplies under high power density. Moreover, the thermal conductivity of the magnetic material and the silicon dioxide layer is better than that of epoxy resin, polyester resin, anhydride catalyst, and paraffin, so it can also effectively improve the thermal conductivity of the PCB board of the planar transformer, which is beneficial to the heat dissipation of the copper circuit in the PCB board of the planar transformer.

[0013] By adopting the above scheme, the present invention provides a magnetic prepreg of a PCB board of a planar transformer and a preparation method thereof. Since the magnetic prepreg contains magnetic material and the magnetic material is coated with silicon dioxide, it can have magnetism while satisfying insulation, so it can meet the current demand for high efficiency of switching power supplies under high power density. Moreover, the thermal conductivity of the magnetic material and the silicon dioxide layer is better than that of epoxy resin, polyester resin, anhydride catalyst, and paraffin, so it can also effectively improve the thermal conductivity of the PCB board of the planar transformer, which is beneficial to the heat dissipation of the copper circuit in the PCB board of the planar transformer. DETAILED DESCRIPTION

[0014] The present invention is described in detail below in conjunction with specific embodiments.

[0015] Example 1

[0016] This embodiment provides a magnetic prepreg of a PCB board of a planar transformer, and the preparation method is as follows: the magnetic material composition is selected to be 79.6wt% Fe, 9.5wt% Si, 7.5wt% Cr, 3.0wt% B, 0.05-0.2wt% Al, 0.1wt% C, and 0.1wt% Mn, wherein the particle size of the magnetic material is 3-10um. The magnetic material is mixed with a microemulsion prepared by mixing a surfactant, n-hexanol, cyclohexane and water, and then tetraethyl orthosilicate (TEOS) and ammonia water are added in sequence, stirred at 50°C for 6 hours and then dried to form a coated powder; wherein the surfactant is preferably phenyl-polyethylene glycol, wherein the addition ratio is 0.5wt% of the weight of the magnetic material powder, wherein the addition ratio of n-hexanol is 2wt% of the weight of the magnetic material powder, wherein the addition ratio of cyclohexane is 10wt% of the weight of the magnetic material powder, wherein the addition ratio of tetraethyl orthosilicate is 0.3wt% of the weight of the magnetic material powder, wherein the addition ratio of ammonia water is 0.05wt% of the weight of the magnetic material powder, and wherein the addition ratio of water is 0.5wt% of the weight of the magnetic material powder. The coated powder is mixed with 1-3um oxide, epoxy resin, polyester resin, anhydride catalyst and paraffin to obtain a mixed powder; wherein the 1-3um oxide is preferably silicon oxide, wherein the addition ratio of the 1-3um oxide is 10wt% of the weight of the coated powder, wherein the epoxy resin accounts for 15wt% of the weight of the coated powder, wherein the polyester resin accounts for 15wt% of the weight of the coated powder, wherein the anhydride catalyst accounts for 0.1wt% of the weight of the coated powder. The addition ratio of paraffin is 0.5wt% of the weight of the coated powder. The mixed powder is heated and stirred for 5 hours under a nitrogen atmosphere, the heating temperature is greater than the melting temperature of the paraffin, and after cooling, it is crushed into powder by a crusher to obtain granulated powder. The particle size of the granulated powder is between 50um and 300um. The granulated powder is pressed and molded by a pressure of 50MPa to obtain a magnetic sheet embryo, and the magnetic sheet embryo is cured for 30 minutes under a nitrogen atmosphere at 200°C to form a magnetic semi-cured sheet.

[0017] Embodiment 2:

[0018] This embodiment provides a magnetic prepreg of a PCB board of a planar transformer, and the preparation method is as follows: the magnetic material composition is selected to be 86.85wt% Fe, 6.5wt% Si, 5.5wt% Cr, 1.0wt% B, 0.05wt% Al, 0.05wt% C, and 0.05wt% Mn, wherein the particle size of the magnetic material is 3-10um. The magnetic material is mixed with a microemulsion prepared by mixing a surfactant, n-hexanol, cyclohexane and water, and then tetraethyl orthosilicate (TEOS) and ammonia water are added in sequence, stirred at 50°C for 2 hours and then dried to form a coated powder; wherein the surfactant is preferably phenyl-polyethylene glycol, wherein the addition ratio is 2.5wt% of the weight of the magnetic material powder, wherein the addition ratio of n-hexanol is 5wt% of the weight of the magnetic material powder, wherein the addition ratio of cyclohexane is 20wt% of the weight of the magnetic material powder, wherein the addition ratio of tetraethyl orthosilicate is 2.0wt% of the weight of the magnetic material powder, wherein the addition ratio of ammonia water is 0.1wt% of the weight of the magnetic material powder, and wherein the addition ratio of water is 2.0wt% of the weight of the magnetic material powder. The coated powder is mixed with 1-3um oxide, epoxy resin, polyester resin, anhydride catalyst and paraffin to obtain a mixed powder; wherein the 1-3um oxide is preferably silicon oxide, wherein the addition ratio of the 1-3um oxide is 20wt% of the weight of the coated powder, wherein the epoxy resin accounts for 5wt% of the weight of the coated powder, wherein the polyester resin accounts for 5wt% of the weight of the coated powder, wherein the anhydride catalyst accounts for 0.01wt% of the weight of the coated powder. The addition ratio of paraffin is 2.0wt% of the weight of the coated powder. The mixed powder is heated and stirred for 1 hour under a nitrogen atmosphere, the heating temperature is greater than the melting temperature of the paraffin, and after cooling, it is crushed into powder by a crusher to obtain granulated powder. The particle size of the granulated powder is between 50um and 300um. The granulated powder is pressed and molded by a pressure of 50MPa to obtain a magnetic sheet embryo, and the magnetic sheet embryo is cured for 90 minutes in a nitrogen atmosphere at 160°C to form a magnetic semi-cured sheet.

[0019] Embodiment 3:

[0020] This embodiment provides a magnetic prepreg of a PCB board of a planar transformer, and the preparation method is as follows: the magnetic material composition is selected to be 82.7wt% Fe, 8.5wt% Si, 6.5wt% Cr, 2.0wt% B, 0.15wt% Al, 0.08wt% C, and 0.07wt% Mn, wherein the particle size of the magnetic material is 3-10um. The magnetic material is mixed with a microemulsion prepared by mixing a surfactant, n-hexanol, cyclohexane and water, and then tetraethyl orthosilicate (TEOS) and ammonia water are added in sequence, stirred at 50°C for 4 hours and then dried to form a coated powder; wherein the surfactant is preferably phenyl-polyethylene glycol, wherein the addition ratio is 1.8wt% of the weight of the magnetic material powder, wherein the addition ratio of n-hexanol is 3wt% of the weight of the magnetic material powder, wherein the addition ratio of cyclohexane is 15wt% of the weight of the magnetic material powder, wherein the addition ratio of tetraethyl orthosilicate is 1.2wt% of the weight of the magnetic material powder, wherein the addition ratio of ammonia water is 0.08wt% of the weight of the magnetic material powder, and wherein the addition ratio of water is 1.3wt% of the weight of the magnetic material powder. The coated powder is mixed with 1-3um oxide, epoxy resin, polyester resin, anhydride catalyst and paraffin to obtain a mixed powder; wherein the 1-3um oxide is preferably aluminum oxide, wherein the addition ratio of the 1-3um oxide is 15wt% of the weight of the coated powder, wherein the epoxy resin accounts for 10wt% of the weight of the coated powder, wherein the polyester resin accounts for 8wt% of the weight of the coated powder, wherein the anhydride catalyst accounts for 0.05wt% of the weight of the coated powder. The addition ratio of paraffin is 1.5wt% of the weight of the coated powder. The mixed powder is heated and stirred for 3 hours under a nitrogen atmosphere, the heating temperature is greater than the melting temperature of the paraffin, and after cooling, it is crushed into granulated particles by a crusher. The particle size of the granulated particles is between 50um and 300um. The granulated powder is pressed and molded by a pressure of 50MPa to form a magnetic sheet embryo, and the magnetic embryo is cured for 60 minutes under a nitrogen atmosphere at 185°C to form a magnetic semi-cured sheet.

[0021] Comparative Example 1:

[0022] The present comparative example provides a PCB board semi-cured sheet, and the preparation method is as follows: 1-3um oxide is mixed with epoxy resin, polyester resin, anhydride catalyst, and paraffin to obtain a mixed powder; wherein the 1-3um oxide is preferably silicon oxide, wherein the addition ratio of the 1-3um oxide is 35wt% of the total weight, wherein the epoxy resin accounts for 32wt% of the total weight, wherein the polyester resin accounts for 31.2wt% of the total weight, wherein the anhydride catalyst accounts for 0.3wt% of the total weight, wherein the addition ratio of paraffin is 1.5wt% of the total weight. The mixed powder is heated and stirred for 3 hours under a nitrogen atmosphere, the heating temperature is greater than the melting temperature of the paraffin, and after cooling, it is crushed into granulated particles by a crusher. The particle size of the granulated particles is between 50um and 300um. The granulated powder is pressed and molded by a pressure of 50MPa to form an embryo, and the embryo is cured for 60 minutes under a nitrogen atmosphere at 185°C to form a semi-cured sheet.

[0023] In order to facilitate the testing of the embodiments and comparative examples, the magnetic semi-cured sheets obtained in Examples 1-3 were respectively made into performance test cores, and the test cores were magnetic rings, and the size of the magnetic rings was outer diameter (OD) * inner diameter (ID) * thickness (TH) = 20.0mm * 12.0mm * 1.0mm. The annealed magnetic rings were tested for the initial magnetic permeability μ (1MHz) of the magnetic ring samples using an inductance precision analyzer, and the magnetic ring breakdown voltage was tested using a DSM-8104 insulation withstand voltage tester. The semi-cured sheets obtained in the comparative example were made into comparative example cores according to the size of the test cores.

[0024] Table 1. Performance comparison of Examples 1-3 and Comparative Examples

[0025] Test items Parameter Unit Example 1 Example 2 Example 3 Comparative Example Magnetic Permeability - 3 5 4 1 Breakdown voltage V >1600V >1600V >1600V >1600V

[0026] The materials prepared in Examples 1-3 and the comparative example have a better magnetic permeability than the comparative example at a breakdown voltage greater than 1600V, so in practical applications, they are beneficial to reducing copper loss in planar transformers and thus have the advantage of low power consumption, thereby improving the conversion efficiency of product application circuits. This shows that component control and process treatment are very important for low-loss inductors.

[0027] In summary, the present invention provides a magnetic prepreg of a PCB board of a planar transformer and a preparation method thereof. Since the magnetic prepreg contains a magnetic material and the magnetic material is coated with silicon dioxide, it can have magnetism while satisfying insulation, and thus can meet the current demand for high efficiency of switching power supplies at high power density. Moreover, the thermal conductivity of the magnetic material and the silicon dioxide layer is better than that of epoxy resin, polyester resin, anhydride catalyst, and paraffin, so it can also effectively improve the thermal conductivity of the PCB board of the planar transformer, which is beneficial to the heat dissipation of the copper circuit in the PCB board of the planar transformer.

[0028] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a magnetic prepreg of a PCB board of a planar transformer, characterized in that: The following steps are involved: S1: coating a magnetic material with a particle size less than 20 μm with a layer of silicon dioxide to form a coated powder; S2: mixing the coated powder with epoxy resin, polyester resin, anhydride catalyst and paraffin to obtain a mixed powder; S3: heating and stirring the mixed powder in an inert gas atmosphere to uniformly obtain granulated powder after cooling; the mixed powder is crushed into powder to obtain granulated powder; the heating temperature is greater than the melting temperature of paraffin; S4: the granulated powder is pressed under a pressure of 10-100 MPa to obtain a magnetic sheet embryo; S5: semi-curing the magnetic sheet embryo under an inert gas atmosphere at 140-250° C. to form a magnetic semi-cured sheet; The magnetic material composition is 79.6-86.85wt% Fe, 6.5-9.5wt% Si, 5.5-7.5wt% Cr, 1.0-3.0wt% B; the magnetic material also includes: 0.05-0.2wt% Al, 0.05-0.1wt% C, 0.05-0.1wt% Mn; In step S2, it also includes: adding an oxide with a particle size less than 5 μm to mix with the coated powder, the oxide is silicon oxide and / or aluminum oxide, the addition amount of the oxide is 10wt% to 20wt% of the coated powder, wherein the addition amount of epoxy resin is 5wt% to 15wt% of the coated powder, wherein the addition amount of polyester resin is 5wt% to 15wt% of the coated powder, wherein the addition amount of anhydride catalyst is 0.01wt% to 0.1wt% of the coated powder, and wherein the addition amount of paraffin is 0.5wt% to 2.0wt% of the coated powder.

2. The method for preparing a magnetic prepreg of a PCB board of a planar transformer according to claim 1, characterized in that: The preparation method of the coated powder is: mixing the magnetic material and the hydrolysis component to undergo a hydrolysis reaction at 35-75°C, and then drying to form the coated powder; wherein the hydrolysis component is: tetraethyl orthosilicate and ammonia water; wherein the addition amount of tetraethyl orthosilicate is 0.3wt% to 2.0wt% of the magnetic material, and wherein the addition amount of ammonia water is 0.05wt% to 0.1wt% of the magnetic material.

3. The method for preparing a magnetic prepreg of a PCB board of a planar transformer according to claim 2, characterized in that: The hydrolysis components also include: surfactants, alcohol solvents, alkane solvents, and water. The surfactant is added in an amount of 0.5wt% to 2.5wt% of the magnetic material, the alcohol solvent is added in an amount of 2wt% to 5wt% of the magnetic material, the alkane solvent is added in an amount of 10wt% to 20wt% of the magnetic material, and the water is added in an amount of 0.5wt% to 2.0wt% of the magnetic material.

4. The method for preparing a magnetic prepreg of a PCB board of a planar transformer according to claim 3, characterized in that: The specific steps of step S1 are: S11: mixing magnetic powder, surfactant, alcohol solvent, alkane solvent and water and stirring to prepare a microemulsion containing magnetic powder; S12: adding tetraethyl orthosilicate to the microemulsion containing magnetic powder and continuing to stir; S13: adding ammonia water to hydrolyze tetraethyl orthosilicate and coat a layer of silicon dioxide on the surface of the magnetic material.

5. The method for preparing a magnetic prepreg of a PCB board of a planar transformer according to claim 3, characterized in that: The surfactant is phenyl-polyethylene glycol, the alcohol solvent is n-hexanol, and the alkane solvent is cyclohexane.

6. The method for preparing a magnetic prepreg of a PCB board of a planar transformer according to claim 1, characterized in that: The mixed powder is heated and stirred for 1 to 5 hours in an inert gas atmosphere, and the particle size of the granulated powder is 50 um to 300 um; the inert gas is nitrogen.

7. A magnetic prepreg for a PCB board of a planar transformer, characterized in that: The magnetic prepreg of the PCB board of the planar transformer is prepared by the preparation method of any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of insulation coated composite powder and transformer core

    CN109014177A

  • Resin composition, cured resin, sheet-like cured resin, laminated body, prepreg, electronic parts and multilayer boards

    CN1732224A